UPAYA GURU MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA KELAS V DENGAN PENDEKATAN INTERAKTIF MATERI DAILY ACTIVITY (STUDI KASUS DI SDN MERGOSONO 3 KOTA MALANG) - Ima Mukarromah; Devi Wahyu Ertanti; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is about the efforts made by the teacher in improving student’s English speaking ability who relatively low, and there are still many students who do not listen to their teachers because they are bored with material taught and learning model. That’s why the teacher improving stutednt’s english speaking ability with interactive approach. The research method used is qualitative research. Data collection techniques used were observation, interviews, documentation and quetioner. Which is analyzed by document reduction, document presentation, conclusion drawing. This reearch was found that the student's speaking ability increased significantly.  Therefore, it concluded that the student's English speaking ability can be improved by using interactive approach. The finding lead to the recomendation for the teachers to use interactive approach as an alternative model in teaching speaking English ability. It also recomended to other researcher for continue research.